PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI EKOSISTEM - Fatari, Imelda Trivany; Ningsih, Kurnia; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study seeks to ascertain how learning is implemented and enhance student learning outcomes. By using the discovery learning model on ecosystem content for class X A at SMA Kemala Bhayangkari 1 Kubu Raya. Classroom Action Research (CAR), which was conducted in two cycles with four steps each planning, action implementation, observation, and reflection is included in this study. Thirty students served as research participants, and learning observation sheets and learning outcome examinations were used as data gathering tools. In all cycles, learning was implemented 100% in accordance with the teaching module. From Cycle I, which had an average score of 78.44 and a completion rate of 76.67%, to Cycle II, which had an average score of 88.67 and a completion rate of 86.67%, the results demonstrated an increase in student learning outcomes. These results show that using the discovery learning model effectively enhances students' comprehension and abilities while also promoting their active participation in the educational process. Thus, the discovery learning model not only helps students understand the concept of ecosystems more deeply, but also fosters learning independence and critical thinking skills.